Rowing Against the Tide: The Struggle to Raise Union Density in a Hostile Environment - Jackson, Andrew (Paths to Union Renewal: Canadian Experiences, 2006)
[P]rovides an overview of the trends and patterns of union density in Canada and its implications for union renewal. Of particular interest is [the author's] analysis of the opportunities for new organizing in various industries and occupations. –Editors' introduction
Keywords: Labor Unions; Labor movement; Organizational change